Volatility Triggered Range Forward (VTRF): an instrument for protection against volatility fluctuations in the BRL/USD pair - Bovo, Vitor Juliano (2011)
This work proposes an instrument able to absorb shocks in the BRL/USD rate, ensuring its holder the capability of doing foreign currency exchange at some immediate prevailing rate. The Volatility Triggered Range Forward resembles a plain-vanilla forward whose delivery price is unknown initially and will be set once a pre-determined level of volatility threshold is reached in the exchange rate along the instrument’s life. Its payoff schedule can be set for any number of periods. Pricing and risk management is based on a trinomial lattice weighted between two possible regimes of volatility. These regimes are determined after a study of the BRL/USD series for the period between 2003 and 2009, based on a Switching Autoregressive Conditional Heteroskedasticity (SWARCH) model.